The Participatory Roles of Monks in Driving The Sufficiency Economy in the Northeastern Region. - Ketnakorn, PhrabaidikaSuphot (Journal of International Buddhist Studies, 2017)
The research objective of this study include the study of participation driven sufficiency economy and present the form of participation in driven sufficiency economy of the Buddhis monk in the Northeast. The researcher used mixed method which is a qualitative research and quantitative research. The samples are Buddhist monks and people which consisted of nine provinces, including 368 monks from Ubon Ratchathani, Amnat Charoen, Nakhon Phanom, Khon Kaen, Nong Khai, Nakhon Ratchasima, Buri Ram, Surin and Roi Et. The researchers collected data by using questionnaires Interviews and informal interview.